A Rare Case of Rivaroxaban Causing Delayed Symptomatic Hepatocellular Injury and Hyperbilirubinemia - Keith Glenn; Patrick Chen; Mustafa Musleh; Rao Pallivi; Melissa Grilliot (Case Reports in Gastrointestinal Medicine)
Importance. As Rivaroxaban has increased in popularity, it has been accompanied with a growing body of evidence displaying its ability to cause drug induced liver injury (DILI). Observation. A 74-year-old Caucasian female developed Rivaroxaban DILI two weeks after finishing a 14-day course. The patient was symptomatic and jaundiced with elevated transaminases and hyperbilirubinemia with normal lab values two months priorly. Liver biopsies showed mixed inflammatory infiltrate of lymphocytes, neutrophils and eosinophils, rare necrotic hepatocytes, and canalicular and intrahepatocellular cholestasis, all of which are consistent with DILI. Conclusion and Relevance. We present this case to add to the growing evidence that Rivaroxaban can be associated with severe, symptomatic liver injury and to ensure physicians are aware of these possible side effects of novel anticoagulants with their increasing use.